A hundred years of the IAPR : a celebratory supplement to the Archive for the Psychology of Religion : studies and discussions of the history of the International Association for the Psychology of Religion - Belzen, J. A. van 1959- (Religious Studies, Theology and Philosophy E-Books Online, Collection 2016, ISBN: 9789004303942., 2016)
In 2015, both the journal Archive for the Psychology of Religion and the International Association for the Psychology of Religion (IAPR), the bearer of the journal, completed their first century. This occasion prompted extensive historical research to the scientific infrastructure concerned, and critical reflection on their reason for existence, dealing with questions such as: How is the psychology of religion doing? What is it about? Which factors play a role? Whom does it serve? What has been the place and value of the infrastructure now celebrating its existence? This celebrating supplement to the Archive for the Psychology of Religion expands this discussion of IAPR's history and continues its critical reflexion.